Cross-culture adaptation and validation of knowledge, attitude and behavior regarding disaster preparedness among community in Indonesia - Fatoni Fatoni; Santhna Letchmi Panduragan; Tukimin Sansuwito; Lenny Stia Pusporini (Jurnal Keperawatan Padjadjaran, 2023)
Background: At the time of the research, there were only a limited number of instruments accessible for recognizing the knowledge, attitude, and behavior of the Indonesian population concerning disaster preparedness. Objectives: The goal of this study was to modify and evaluate the reliability and uniformity of a survey that individuals can complete on their own, focusing on their knowledge, attitude, and behavior related to disaster preparedness. Methods: The translation of this tool into Bahasa Indonesia went through four phases: first translation, back-translation by experts, pre-testing, and cognitive interviews. The evaluation of the tool's accuracy involved a study with 250 volunteers using a cross-sectional approach. The validity of the questionnaire was checked based on its content and structure, and its reliability was measured by looking at internal consistency and stability (Cronbach's alpha). Results: The CVI scores for knowledge, attitude, and behaviors ranged from 0.80 to 1.00. Regarding knowledge, the exploratory factor analysis (EFA) outcomes indicated the presence of two factors with eigenvalues surpassing 1.0, collectively explaining 71.4% of the total variance. The loading factor for 25 items was observed between 0.34 and 0.65, within the acceptable threshold of 0.3. In terms of attitude, the EFA results revealed a single factor with an eigenvalue exceeding 1.0, accounting for 86.2% of the total variance. The loading factor for 18 items ranged from 0.30 to 0.50. Similarly, for behaviors, the EFA findings displayed the existence of two factors with eigenvalues greater than 1.0, explaining a cumulative 79.7% of the total variance. The loading factor for 22 items ranged from 0.30 to 0.60. The Cronbach's alpha values for knowledge regarding earthquake and tsunami preparedness stood at 0.763, for attitude it was 0.736, and for behaviors, it was 0.760. Conclusion: The recently implemented scale designed to assess the knowledge, attitude, and behavior of communities regarding disaster preparedness has been verified to possess satisfactory validity and reliability, making it suitable for survey applications within Indonesia.